2016
DOI: 10.2147/jaa.s111170
|View full text |Cite
|
Sign up to set email alerts
|

Historical cohort study examining comparative effectiveness of albuterol inhalers with and without integrated dose counter for patients with asthma or chronic obstructive pulmonary disease

Abstract: BackgroundUsing a metered-dose inhaler (MDI) beyond the labeled number of actuations may result in inadequate dosing of medication, which can lead to poor clinical outcomes. This study compared respiratory-related emergency department (ED) visit rates in patients with asthma, chronic obstructive pulmonary disease, or both when they used albuterol MDIs with versus without dose counters.MethodsThis retrospective study used US claims data to identify patients (ages 4–64 years) with asthma, chronic obstructive pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(15 citation statements)
references
References 20 publications
2
13
0
Order By: Relevance
“…Although in the current study eosinophil counts were not assessed as a risk factor, it was demonstrated that the proportion of patients experiencing ≥1 exacerbations during the follow-up period was higher in patients who had severe uncontrolled asthma (GINA Step 4/5 plus ≥2 exacerbations in the previous year) with eosinophil counts (≥300 cells/μl) than in patients who did not. The current study also demonstrated that females had a higher exacerbation risk than males, a result demonstrated in a previous study, [20] although not all studies are in agreement [21]. …”
Section: Discussionsupporting
confidence: 83%
“…Although in the current study eosinophil counts were not assessed as a risk factor, it was demonstrated that the proportion of patients experiencing ≥1 exacerbations during the follow-up period was higher in patients who had severe uncontrolled asthma (GINA Step 4/5 plus ≥2 exacerbations in the previous year) with eosinophil counts (≥300 cells/μl) than in patients who did not. The current study also demonstrated that females had a higher exacerbation risk than males, a result demonstrated in a previous study, [20] although not all studies are in agreement [21]. …”
Section: Discussionsupporting
confidence: 83%
“…Consistent with our findings, a historical cohort study of 75,787 patients with asthma aged 4–64 years (53,964 using albuterol with a dose counter and 21,823 using albuterol without a dose counter) by Price et al demonstrated that patients using an inhaler with a dose counter had a 51% lower incidence of respiratory-related ED visits (adjusted rate ratio: 0.49; 95% CI 0.41–0.59) 22. The authors speculated that the albuterol dose counters may have enabled patients to determine when their rescue medication was empty, and/or when additional controller adherence was needed, thus preventing them from using an empty inhaler during an asthma exacerbation 22. The addition of a dose counter can help to reduce ED visits, thereby reducing health care costs associated with asthma.…”
Section: Discussionsupporting
confidence: 91%
“…The use of IDCs may contribute to improvements in the control of respiratory disease and respiratory-related health care utilization and costs. Results from a real-world study demonstrated reduced incidence of respiratory-related ED visits in patients using rescue inhalers with IDC compared to those with no dose counter on their inhalers 22. However, there is paucity of data on the real-world impact of ProAir HFA equipped with dose counters on HRU among patients with asthma.…”
Section: Introductionmentioning
confidence: 99%
“…Increased eosinophils are associated with increased disease severity, more exacerbations and less well-controlled asthma [2023]. Therefore, these patients may be eligible for treatment with biologics.…”
Section: Introductionmentioning
confidence: 99%